THE CORRELATION BETWEEN TEACHERS’ PROFESSIONALISM AND STUDENTS’ LEARNING ACHIEVEMENT AT SMP NEGERI 2 WABULA - Agusrian Hatma; La Mido; Nety Nety (English Education Journal, 2020)
The problem statement in this research was whether there was correlation between teacher’s professionalism and syudents’ learning achievemen. The objective of this research was to find out the correlation between teachers’ professionalism and students’ learning achievement. The type of this research was a quantitative research. The population on this research was all students at grade VIII of SMP Negeri 2 Wabula with total sample of this research was 24 students by using total sampling technique. In collecting data, the researcher used questionnaire and test. The result of this research showed that at the significance level, the score of rcount was 0.784 and rtable was 0.433, it meant that rcount more than rtable, this showed there was significant correlation between teacher’s professionalism and students’ learning achievement at SMP Negeri 2 Wabula. Also, the coefficient determination was 0.614. it meant that the contribution of teachers’ proffesinalism for students’ learning achievement at SMP Negeri 2 Wabula for 61.4%, meanwhile the rest for 39.6% was other factors. Then, the correlation between teacher’s professionalism and students’ learning achievement at SMP Negeri 2 Wabula was 0.784, it was the strong correlation because it was in the range 0.600-0.799.